Financial risk management for dummies - Brown, Aaron, 1956- (--For dummies., 2016)
Take the risk out of financial risk management Written by bestselling author and past winner of the GARP Award's Risk Manager of the Year, Aaron Brown, Financial Risk Management For Dummies offers thorough and accessible guidance on successfully managing and controlling financial risk within your company. Through easy-to-follow instruction, you'll find out how to manage risk, firstly by understanding it, and then by taking control of it. Plus, you'll discover how to measure and value financial risk, set limits, stop losses, control drawdowns and hedge bets. Financial risk management uses financial instruments to manage exposure to risk within firms, large and small particularly credit risk and market risk. From managing and measuring risk to working in financial institutions and knowing how to communicate risk to your company and clients, Financial Risk Management For Dummies makes it easy to make sense of the management of risk when working in various different financial institutions and concludes by covering the topic of how to communicate risk how to report it properly and how to deal with and comply with all of the regulations.